Censoring or Queering? TV-Subtitling of South Park in Türkiye - Cihan Alan (İstanbul Üniversitesi Çeviribilim Dergisi)
TV subtitles are mostly euphemized and ideologically recontextualized with individual and/or institutional motivations for the target viewer in Türkiye due to varying socio-cultural and political factors. Accordingly, subtitlers are faced with challenges in providing adequate translations for source taboo language, including sexually explicit swearwords and vulgar slang. However, censorship policies in AVT may conversely urge translators to be involved in a more creative process, which may, in turn, result in the subversion of the very censorious discourse. The aim of this study is to investigate censorship as an ideological and translation constraint in TV subtitling, as well as a factor laying the grounds for creating possible meanings in subtitling. To this end, a descriptive analysis was conducted based on the TV subtitles of South Park, an American sitcom animation show. The analysis shows that institutional norms force translators to be creative in transferring the taboo language to preserve humorous and obscene narrative content, which appears as a queer effort whereby the taboo meaning is destabilized, particularly in the case of references to sexual organs and homosexuality. The qualitative and quantitative analyses provide an overview of the translation strategies employed and the pragmatic effect created by freelance subtitlers translating for private media institutions from English into Turkish in the case of the taboo language. The case presented in this study can also give an insight into the translator’s performativity in AVT through which meanings are created in the target culture under repressive circumstances.